2021
DOI: 10.1186/s12879-021-06795-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among GLASS priority pathogens from Pakistan: 2006–2018

Abstract: Background In 2018 Pakistan initiated its national antimicrobial resistance (AMR) surveillance aligned with Global Antimicrobial Surveillance System (GLASS). To complement this surveillance, we conducted a situational analysis of AMR rates among GLASS organisms in the country. Data from published studies and from antibiograms was compared and role of antibiograms as potential contributors to national AMR surveillance explored. Methods AMR rates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…However, we could not draw any conclusive remark on it because of the low number of samples tested. Very recently published research on shigellosis also observed increasing resistance to ceftriaxone [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not draw any conclusive remark on it because of the low number of samples tested. Very recently published research on shigellosis also observed increasing resistance to ceftriaxone [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMR is a particular issue in low- and middle-income countries (LMICs); however, the data describing the economic loss as well as mortality due to AMR in these countries are scarce [ 6 , 7 ]. Pakistan is no exception with, for instance, 64% extensively drug-resistant (XDR) cases of tuberculosis were recently identified [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant (MDR) pathogens are making common infections more di cult to treat or untreatable, and burdensome to the health care system. Studies have shown increased prevalence of ESBL producing strains and carbapenem resistance strains among blood pathogens [7][8][9]. The MDR patterns of bacterial isolates from our study clearly suggest that ESBL producing strains may be circulating at LCH.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, surveillance of bloodstream infections from blood cultures and their antibiotic resistance patterns are vital to the care of patients and prevention of BSI [2]. Studies have shown increased prevalence of extended spectrum beta lactamase (ESBL) producing strains and carbapenem resistance strains among blood pathogens [7][8][9].…”
Section: Introductionmentioning
confidence: 99%